Effect of Saline Organic Acid Solutions Applied During Wheat Tempering on Flour Functionality. Issue 3 (9th January 2017) - Sabillón, Luis; Bianchini, Andréia; Stratton, Jayne; Rose, Devin J.
Abstract : Previously, we showed that tempering with saline organic acid solutions can reduce the aerobic plate count of wheat by as much as 4.3 log CFU/g. The purpose of this study was to evaluate the impact of these tempering solutions on the functional properties of resulting whole grain (WGF) and straight‐grade (SGF) flours. Wheat was tempered to 15.5% moisture by tempering with sterile distilled water (control) or solutions containing NaCl (26% [w/v]) together with organic acid (acetic or lactic 2.5 and 5.0% [v/v]). After milling, fractions were collected and recombined as needed to obtain WGF or SGF. The acid content in WGF was higher than in SGF, indicating limited penetration of the organic acids into the endosperm of the grain. In WGF, the saline organic acid treatments caused a decrease in paste viscosity and bread crumb cell sizes in breads. In SGF, the saline organic acid treatments caused significant changes in paste viscosity and some Mixograph parameters; however, principal components analysis indicated that the treatments did not substantially affect SGF functionality. Thus, WGF was altered by the saline organic acid solutions, whereas SGF functionality was minimally affected by tempering treatments, perhaps because of acids only partially penetrating into the endosperm.